Step up in the Neonatal Resuscitation Program (NRP). Updates from NRP 7th edition - Mohamed, Mossad Abdelhak Shaban; Hasan, Taufiq Hidayat; Abu Bakar, Asrar; Anuar, Muhamad Azamin; Raza, Habibalam; Elghuwael, Ismail (2019)
Background: At birth, almost 10% of newborn need intervention. The golden minutes to save the brain and vital organs are time-critical. Presentation: qualified person or resuscitation team should attend every delivery. Antepartum communication with the obstetric team gathering knowledge about maturity, amniotic fluid, number of foetuses, and other risk factors. The assigned team perform briefing, delegate workload, and check equipment. Upon delivery, it is vital to perform a rapid assessment is the baby - term, muscle tone and breathing or crying. Then commencing the initial steps of warming, sniffing position, suction, drying and stimulation. Use plastic wrap for less than 32 weeks. If the baby got abnormal respiration or HR, lung Ventilation and Ventilation Corrective Steps (MRSOPA) is the critical step with early use pulse oximetry and electronic cardiac monitor. Adjust suction pressure from 60-100 and the flowmeter to 10 L/min. Start oxygen with 21%, adjusting preductal saturation within the target zone. Use a resuscitation device capable of providing PEEP and CPAP. Continue PPV 40-60 breaths/minute until spontaneous effort. If heart rate less than 60 spite of effective 30-second ventilation intubate, start chest compression for 60 seconds by two thumbs technique. If still bradycardic, an urgent UVC/IO access and medications with adrenaline, normal saline or 0 negative blood as needed. It is important to consider special situations especially pneumothorax. Conclusion: NRP is evolving according to evidence-based medicine; all institutions should retrieve the latest NRP edition. Key behavioural skills including call for help, will lead to successful resuscitation.